The Hierarchical Three-Dimensional (3D) Dynamic Water Infiltration on Multi-layers of Soil According to Voronoi Sequence Nodes Based on the Three-Dimensional Triangular Irregular Network (3D TIN) - Siti Nurbaidzuri, Reli @ Raily; Izham, Mohamad Yusoff; Habibah, Lateh; Muhamad Uznir, Ujang (Springer Cham, 2017)
Understanding soil water infiltration movement has been birthed from extensive interest and concern in the last few decades. The arrangement of particles (i.e. structures and sizes) and the interaction between both the soil and soil water have a profound effect on the soil water infiltration. The challenging task in the soil fluid modelling is the indeterminate spatial extent that has no specific boundaries and the fact that it is difficult to sense. Plenty of investigations and studies have been conducted to measure the water movement. However, less focus has been given on the movement of the dynamic soil water infiltration. This paper will focus on modelling the three-dimensional (3D) soil water infiltrations that flow downward due to the gravitational factor and gradient pressure. The 3D hierarchical soil water infiltration model proposes the integration of techniques which includes the Tree-map to isolate the depth of the soil that acts as a route of the soil water flow from the surface of the terrain to the subsurface flow. Moreover, the 3D Gosper curve is used to represent the soil water flow pattern that is based on the law of gravity and Horton equation, which control the flow of the soil water in the model. The curves that consist of a series of nodes adopt the Three-Dimensional Triangular Irregular Network (3D TIN) which creates a network of flow direction that allows the water to pass through the nodes according to a predetermined sequence. The study area has an average of 8.5 mm total rain and −5 m water level. The soil is divided into a few layers to represent the flow of the soil water according to the sequence of nodes. The soil depth (40, 80, 120, 160 and 200 cm) isolation in the form of Voronoi-shaped polygon nodes allows the soil water to flow down where the depth is chosen based on the soil wetting range of the subsurface soil.